CiD4HMOS: A Solution to HarmonyOS Compatibility Issues - Ma, Tianzhi; Zhao, Yanjie; Li, Li; Liu, Liang (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2023)
HarmonyOS is an operating system boasting a substantial global user base and provides multiple versions of its SDK. Various open-source applications continue to utilize older versions, leading to compatibility issues arising from system constraints. These prevalent issues can substantially affect the user experience. Although numerous solutions have been suggested for addressing compatibility issues in Android, the subject remains largely unexplored within the context of HarmonyOS. To bridge this gap, we investigate the evolution of APIs in HarmonyOS to pinpoint those potentially causing compatibility issues. Based on these insights, we implement CiD4HMOS, a tool designed to detect and categorize compatibility issues in HarmonyOS. We evaluate the feasibility of CiD4HMOS with open-source apps and subsequently apply it to commercially released apps, highlighting its effectiveness in accurately identifying HarmonyOS compatibility issues. The experimental results uncover that CiD4HMOS is effective in detecting compatibility issues in HarmonyOS apps, achieving an accuracy rate of 86.8 % in open-source apps. And, developers of commercially released apps have significantly endorsed our reports. Our research emphasizes the necessity of continuous exploration into compatibility issues within HarmonyOS, underlining the significant role tools like CiD4HMOS play in enhancing the overall user experience.